A WebQuest Example for Mathematics Education - Goktepe, Seda (ELSEVIER SCIENCE BV, 2014)
In this research a WebQuest that can be used in mathematics education is prepared. It was designed to teach coordinate system to seventh grade students in an entertaining way. The prepared WebQuest is published in mathematicswebquest. sitemynet.com web site. The aim of this project is to increase the effectiveness of learning process and enrich the course visually and provide interaction of students. Literature survey method is used in the research. The emergence of WebQuest, preparation process, design steps, important points for effective usage, usage of it in Turkey, advantages & disadvantages and limitations of the system are indicated. The history of WebQuest in Turkey, teacher and student perspectives are also implied in the study. The general view defends that this kind of activities can make a positive contribution on affective and cognitive abilities of learning environments. On the other hand, when the existing structure of studies taken into consideration, some negative situations about the technical deficiencies and teacher/student competence are observed. (C) 2013 The Authors. Published by Elsevier Ltd. Selection and/or peer-review under responsibility of Academic World Education and Research Center.
Keywords: WebQuest; mathematics education; seventh grade students; Education & Educational Research